2015
DOI: 10.1038/srep11789
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mTOR Signaling by Semaphorin 3F-Neuropilin 2 Interactions In Vitro and In Vivo

Abstract: Semaphorin 3F (SEMA3F) provides neuronal guidance cues via its ability to bind neuropilin 2 (NRP2) and Plexin A family molecules. Recent studies indicate that SEMA3F has biological effects in other cell types, however its mechanism(s) of function is poorly understood. Here, we analyze SEMA3F-NRP2 signaling responses in human endothelial, T cell and tumor cells using phosphokinase arrays, immunoprecipitation and Western blot analyses. Consistently, SEMA3F inhibits PI-3K and Akt activity, and responses are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 60 publications
(97 reference statements)
3
63
1
Order By: Relevance
“…More recent studies have demonstrated that this family, including SEMA3 family members, regulate a wider array of cellular activation responses, most notably PI-3K/Akt/mTOR intracellular signaling, migration and proliferation [8183]. Over the past 10 years, several studies have identified SEMA3 receptors, including neuropilin (NRP)-1, NRP-2 and Plexin A family molecules on tumor cells suggesting that they function within the tumor microenvironment to limit cellular migration and growth [80,81,84,85]. Three members of the Class 3 family (SEMA3A, -3C and -3F) also bind NRP’s that are expressed on immune cell types including EC [7578,81], antigen presenting cells [86,87] and CD4 + T cells [70].…”
Section: Class 3 Semaphorins As Novel Intragraft Factors With Potentimentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have demonstrated that this family, including SEMA3 family members, regulate a wider array of cellular activation responses, most notably PI-3K/Akt/mTOR intracellular signaling, migration and proliferation [8183]. Over the past 10 years, several studies have identified SEMA3 receptors, including neuropilin (NRP)-1, NRP-2 and Plexin A family molecules on tumor cells suggesting that they function within the tumor microenvironment to limit cellular migration and growth [80,81,84,85]. Three members of the Class 3 family (SEMA3A, -3C and -3F) also bind NRP’s that are expressed on immune cell types including EC [7578,81], antigen presenting cells [86,87] and CD4 + T cells [70].…”
Section: Class 3 Semaphorins As Novel Intragraft Factors With Potentimentioning
confidence: 99%
“…Over the past 10 years, several studies have identified SEMA3 receptors, including neuropilin (NRP)-1, NRP-2 and Plexin A family molecules on tumor cells suggesting that they function within the tumor microenvironment to limit cellular migration and growth [80,81,84,85]. Three members of the Class 3 family (SEMA3A, -3C and -3F) also bind NRP’s that are expressed on immune cell types including EC [7578,81], antigen presenting cells [86,87] and CD4 + T cells [70]. In general, ligation of the NRP receptor alone is not sufficient to elicit a signal, but serves as co-receptor to activate Plexin A family receptors that in turn elicit potent inhibitory signaling responses [88,89].…”
Section: Class 3 Semaphorins As Novel Intragraft Factors With Potentimentioning
confidence: 99%
See 1 more Smart Citation
“…These, and responses were associated with the disruption of mTOR/rictor assembly and mTOR-dependent activation of the RhoA GTPase. 202 In addition, sema3F also has effects on the tumor microenvironment which contribute to its tumor progression inhibiting ability. It functions as a potent inhibitor of tumor angiogenesis 102,103 and as a result can inhibit tumor progression even when the tumor cells themselves do not express sema3F receptors.…”
Section: 178mentioning
confidence: 99%
“…SEMA3F protein has been shown to compete with VEGFA on NRP2 35 and to inhibit EC functions. 33,40,41 Loss of the functional Sema3F receptor, Nrp2, increased edema and lymphedema after inflammation. This conclusion is based on findings from previous structural studies that have suggested that VEGFA binds between NRP receptor and VEGFR2 in a bridge formation.…”
Section: Discussionmentioning
confidence: 99%